2018
DOI: 10.1002/ccd.27475
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold thrombosis following implantation of the ABSORB BVS in routine clinical practice: Insight into possible mechanisms from optical coherence tomography

Abstract: OCT performed in patients presenting with Absorb ScT demonstrated that malapposition of scaffold struts was more prominent in patients presenting with (very) late ScT, while underexpansion was more frequent in the early cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Several studies have, however, reported that (very) late ScT also frequently occurs between the 2nd and 3rd year after device implantation, and even beyond 3 years, with the latest case of ScT reported as late as 44 months after Absorb BVS implantation [5,6,8,9]. In these studies, the leading mechanisms of very late ScT were associated with (disintegrated) strut material that protruded into the coronary lumen, most likely as a consequence of intraluminal scaffold dismantling or late (acquired) malapposition [10]. DAPT is hypothesised to be an important factor in the prevention of thrombotic events after coronary stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have, however, reported that (very) late ScT also frequently occurs between the 2nd and 3rd year after device implantation, and even beyond 3 years, with the latest case of ScT reported as late as 44 months after Absorb BVS implantation [5,6,8,9]. In these studies, the leading mechanisms of very late ScT were associated with (disintegrated) strut material that protruded into the coronary lumen, most likely as a consequence of intraluminal scaffold dismantling or late (acquired) malapposition [10]. DAPT is hypothesised to be an important factor in the prevention of thrombotic events after coronary stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The threeyear point after Absorb implantation is an important landmark as three years is the approximate period of scaffold polymer absorption 1 . Intraluminal scaffold dismantling and the bioresorption process are possibly underlying mechanisms of VLST 6 . Traces of scaffold have been seen beyond three years; whether DAPT should be continued after three years is still uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the complex process of scaffold degradation and coronary vessel healing, the exact cause of the reported higher rates of (very) late ScT remain partly understood. Early ScT is most often caused by scaffold underexpansion, and late ScT is caused by scaffold malapposition, either pre-existent or acquired 14 .…”
Section: Discussionmentioning
confidence: 99%